2022
DOI: 10.1002/essoar.10512288.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Mesoscale Cloud Morphology in the Shortwave Cloud Feedback

Abstract: The response of low clouds to global warming is one of the largest uncertainties in projections of climate change. Low clouds strongly affect the amount of shortwave radiation reflected back to space from Earth, but do not affect outgoing longwave radiation substantially (e.g., Hartmann & Short, 1980). How clouds alter reflected shortwave radiation in response to warming is termed the shortwave cloud feedback. It is uncertain how low clouds will respond to changes in the atmosphere in a warming world and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(111 reference statements)
1
3
0
Order By: Relevance
“…Our study also attributes the bias in β to cloud morphology, thus providing a more physically grounded perspective rather than the more generic cloud heterogeneity term. I. L. McCoy et al (2022) have shown that environmentally driven transitions between Sc cloud morphologies coincide with variations in thin cloud features, which as shown here, control the magnitude of the bias in β. Future changes in the frequency of occurrence of Sc cloud morphologies could therefore influence the magnitude of RF aci .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our study also attributes the bias in β to cloud morphology, thus providing a more physically grounded perspective rather than the more generic cloud heterogeneity term. I. L. McCoy et al (2022) have shown that environmentally driven transitions between Sc cloud morphologies coincide with variations in thin cloud features, which as shown here, control the magnitude of the bias in β. Future changes in the frequency of occurrence of Sc cloud morphologies could therefore influence the magnitude of RF aci .…”
Section: Discussionsupporting
confidence: 69%
“…Future changes in the frequency of occurrence of Sc cloud morphologies could therefore influence the magnitude of RF aci . Such changes could be attributed to various factors, including cloud feedbacks (I. L. McCoy et al, 2022), changes in cloud thickness resulting from rising CO 2 concentrations (Schneider et al, 2019), and changes in aerosol levels that can influence Sc transitions (Goren et al, 2019(Goren et al, , 2022. Our results also show that for a given cloud albedo, β tends to be larger under more heterogeneous conditions.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Manuscript supporting data is available at https://doi.org/10.5281/zenodo.7311993 (I. L. McCoy & Wood, 2022). CERES Single Scanner Footprint (SSF) daily 1deg product is available at https://asdc.larc.nasa.gov/project/CERES/CER_SSF1deg-Hour_Aqua-MODIS_Edition4A (NASA/LARC/SD/ASDC, 2015).…”
Section: Data Availability Statementmentioning
confidence: 99%